Letter from J.P. Gifford to James Curtis Booth, April 3, 1855 - Gifford, J. P. S. (1855)
A request for information concerning James Curtis Booth's (1810-1888) course offerings.
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers